PENGEMBANGAN MODUL AJAR KURIKULUM MERDEKA - Nengsih, Dona; Febrina, Winda; Maifalinda, Maifalinda; Junaidi, Junaidi; Darmansyah, Darmansyah; Demina, Demina (Komunitas Manajemen Kompetitif, 2024)
The Independent Curriculum teaching module is considered an adequate tool crucial for the smooth implementation of learning with new modes or paradigms, especially if it is associated with the transformation of the industrial and digital revolutions (Maipita et al., 2021). The Independent Curriculum teaching module refers to a number of tools or media facilities, methods, instructions and guidelines that are designed systematically, interestingly and, of course, according to the needs of students. The teaching module itself can be said to be an implementation of the Learning Objectives Flow (ATP) which was developed from Learning Achievements (CP) with the Pancasila Student Profile as the target. Teaching modules are arranged according to the phase or stage of student development. Teaching modules also consider what will be learned with clear learning objectives. Of course, the basis for development is also long-term oriented. Teachers also need to know and understand the concept of teaching modules with the aim of making the learning process more interesting and meaningful. This article was developed using the exposition method with the aim of explaining improving the quality of learning by developing effective teaching modules. The method used is the literature study method Keywords: Learning Quality, Teaching Module